Hypothetics A graphic anthology utilizing the effect of splash pages on the reader's understanding of the story and exploring the splash page as a story telling device - Magat, Rafael Romeo C. (2013)
Splash pages are full page comic panels used to punctuate moments of grandeur and drama in a story. Often maligned for contributing to narrative decompression, its sheer size offers several unexplored narrative possibilities. In order to know what these possibilities might be research was conducted to know the effect that turning every comic book page into splash page had on the reader's understanding of the story. Readers were asked to perform structural analysis on two splash page comics (one silent and one lettered) and the researcher also performed independent structural analyses on various local and foreign comics and a splash page comic. The results showed that the splash page communicated a very clear narrative that did not feel decompressed. Emotions were clearer, environments were more convincing, and anticipation between pages was higher all due to the splash page's size and physical distance from the next page. Not all traditional multi-panel transitions worked however, and words were needed to ensure an easier sense of continuity. Ultimately, the definition of a splash page was broadened to encompass any page in a comic book with only one panel, freeing it from having to deliver only the "big" moments in a comic story. Reader dominance was also proven when they broke the linear reading direction by looking at previous pages. The structural analysis and the interview confirmed that old komiks did not use splash pages and that the reason local comic artists are using them now is due to being exposed to foreign comics. Were the splash page to be fully explored in a long form graphic novel format, newer and more innovative storytelling techniques could be successfully created and the readers would gain an entirely new reading experience.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Comic books, strips, etc. -- Technique